Subsequent vertebral fracture after percutaneous vertebroplasty or kyphoplasty in postmenopausal women with osteoporotic vertebral compression fracture - Zhang, Qianru; Cheng, Yuanpei; Chen, Fengling (Frontiers in Endocrinology, 2026)
BackgroundSubsequent vertebral fracture (SVF) as a severe complication of percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP) for the treatment of osteoporotic vertebral compression fracture (OVCF) is a major public health challenge. Risk factors of SVF following initial PVP or PKP surgery in postmenopausal women are still controversial. This study aims to investigate the risk factors of SVF after initial PVP or PKP for single-level OVCF in postmenopausal women.MethodsPostmenopausal women who were initially treated with PVP or PKP for single-level OVCF were retrospectively analyzed. The patients were divided into SVF group and control group based on whether they had SVF or not. Demographic, surgery-related and radiographic data were recorded from electronic medical records or radiographic examinations. Univariate and multivariate logistic regression analysis were conducted to determine the independent risk factors.ResultsA total of 528 postmenopausal women who met the inclusion and exclusion criteria were included in this study, and 73 postmenopausal women experienced SVF after PVP or PKP. Logistic regression analysis demonstrated that low BMI (OR = 0.905; 95% CI = 0.829-0.987, P = 0.025), previous fracture history (OR = 1.899; 95% CI = 1.046-3.449, P = 0.035) and low BMD (OR = 0.977; 95% CI = 0.966-0.988, P < 0.001) were correlated with SVF following initial PVP or PKP for single-level OVCF in postmenopausal women.ConclusionsLow BMI, previous vertebral fracture history and low BMD were independent risk factors of SVF in postmenopausal women treated with initial PVP or PKP for single-level OVCF.